Efficacy of a cluster randomized controlled parental HIV disclosure intervention trial among parents living with HIV in China: evaluation based on the health action process approach - Li, Xiaoming; Zhang, Ran; Da, Wendi; Zhou, Yuejiao; Shen, Zhiyong; Qiao, Shan (Frontiers in Reproductive Health, 2025)
IntroductionParents living with HIV (PLH) face psychosocial challenges, including disclosing their HIV status to their children. Parental HIV disclosure is critical for reducing stigma, improving psychosocial well-being, and enhancing family cohesion. This study employed the Health Action Process Approach (HAPA) to assess the efficacy of a theory-based intervention aimed at facilitating HIV disclosure among PLH with children aged 6-15 in Guangxi, China.MethodData from a randomized controlled trial involving 791 PLH were analyzed using a multigroup first-order manifest Markov Chain model to investigate transitions through the pre-intention, intention, and action stages over two follow-up periods (6 and 12 months).ResultsThe intervention significantly facilitated progression from pre-intention to action (OR = 3.43; 95% CI: 1.17, 10.01) but did not affect the transition from pre-intention to intention (OR = 1.02; 95% CI: 0.47, 2.20) or influence movement within the intention stage.DiscussionThese findings suggest the need for stage-specific interventions to enhance disclosure practices. Future research should focus on identifying psychosocial predictors of disclosure and adapt interventions to the distinct stages of the disclosure decision-making process.